Dual Mode System of Smart Home Based on Internet of Things - Chico Hermanu; Hari Maghfiroh; Henry Probo Santoso; Zainal Arifin; Catur Harsito (Journal of Robotics and Control (JRC), 2022)
In the digitalization and automation era, the internet has become an inseparable part of human life It provides a place for devices that are connected and can be controlled wirelessly through a network infrastructure, which is called the internet of things (IoT). In this research, the dual mode system of smart home based on IoT is proposed. In this system, the smart home can be controlled both manually and automatically. The key component for the proposed system is the relay mode which can be controlled to select the mode. The hardware implementation was done to test the proposed system with good result. Blynk app is used to control in automatic mode with virtual switch. When the manual mode is selected, the automatic mode is turned off and vice versa.